Factors Affecting The Level Of Financial Inclusion: A Comparative Study Of Tanzania, Kenya And Uganda - Derefa, Moshi James; Swai, Janeth Patrick; Ngollo, Magwana Ibrahim (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This research examined the comparative characteristics affecting financial inclusion in Tanzania, Kenya, and Uganda. Despite Tanzania's robust economic development, its degree of financial inclusion remains inferior to that of its neighboring nations, Kenya and Uganda. The provision of accessible financial services to underrepresented people is essential for poverty alleviation and economic growth. This study used cross-sectional micro-level data from the Global Findex Database survey waves conducted in 2011, 2014, 2017, and 2021. The Least Absolute Shrinkage and Selection Operator (LASSO) post-selection inference technique was used in the research to address issues arising from high-dimensional data and model selection bias. The results indicate that Kenya excels in financial inclusion, propelled by sophisticated digital financial institutions, whilst Tanzania lags behind. The significant primary drivers of financial inclusion were debit card utilization, bank borrowing, and demographic characteristics such as gender and education level while the use of credit cards amongst women had a negative influence on financial inclusion. The research underscores the significance of access to financial services and the contribution of digital finance to improving inclusion. It underscores the need for focused strategies to tackle obstacles such as inadequate infrastructure, insufficient financial literacy, and gender inequities. Research indicates that enhancing mobile money systems and advancing financial literacy, particularly for women and low-income populations, may close the financial inclusion gap. The report emphasizes the need for a more inclusive financial environment to guarantee fair economic growth